Loving the Other: Fantastic Films and Unlikely Couples - Rainey, Sarah Smith (Disability Studies Quarterly, 2019)
This article uses a queer, critical disability studies framework to examine a diverse set of films in which one lover literally changes bodies to be like the other lover, such as in The Little Mermaid (1989), Avatar (2009), and the Twilight saga. The author argues that these films, what she calls "fantastic unlikely couple films," represent the values of companionate love, a relationship form that emphasizes similarity as the key to successful long-term relationships. Significantly, the values of companionate love are aligned with the (neo)liberal state. In the films analyzed, the physically transformed partner is also the weaker, more dependent partner. The shift to a more capable body—one similar to the body of the other partner—not only means that the couple will be more equal companions; it also means that the pair can now fulfill their destiny as productive workers and reproductive parents, independent of state subsidies and assistance.